Comparative Genomics of Trypanosomatid Parasitic Protozoa - El-Sayed, Najib M; Myler, Peter J; Blandin, Gae̊lle; Berriman, Matthew; Crabtree, Jonathan; Aggarwal, Gautam; Caler, Elisabet; Renauld, Hubert; Worthey, Elizabeth A; Hertz-Fowler, Christiane; Ghedin, Elodie; Peacock, Christopher; et al. (Science (American Association for the Advancement of Science), 2005)
A comparison of gene content and genome architecture of Trypanosoma brucei, Trypanosoma cruzi, and Leishmania major, three related pathogens with different life cycles and disease pathology, revealed a conserved core proteome of about 6200 genes in large syntenic polycistronic gene clusters. Many species-specific genes, especially large surface antigen families, occur at nonsyntenic chromosome-internal and subtelomeric regions. Retroelements, structural RNAs, and gene family expansion are often associated with syntenic discontinuities that--along with gene divergence, acquisition and loss, and rearrangement within the syntenic regions--have shaped the genomes of each parasite. Contrary to recent reports, our analyses reveal no evidence that these species are descended from an ancestor that contained a photosynthetic endosymbiont.